Radioimmunoscintigraphy of Tumors Autocrine for Human Met and Hepatocyte Growth Factor/Scatter Factor - Rick V. Hay; Brian Cao; R. Scot Skinner; Ling-Mei Wang; Yanli Su; James H. Resau; George F. Vande Woude; Milton D. Gross (Molecular Imaging, 2002)
Inappropriate expression of the c-met-protooncogene product (Met) and/or of its ligand, hepatocyte growth factor/scatter factor (HGF/SF), has been correlated with poor prognosis in a variety of human solid tumors. We are developing animal models for nuclear imaging of Met and HGF/SF expression in tumors in vivo. We radioiodinated a mixture of monoclonal antibodies (MAbs) that bind to human HGF/SF and to the external ligand-binding domain of human Met, and then injected the I-125-MAb mixture intravenously into mice bearing tumors either autocrine for human HGF/SF and human Met or autocrine-paracrine for murine HGF/SF and murine Met. Serial total body gamma camera images were obtained, and regional activity was determined by quantitative region-of-interest (ROI) analysis. Tumors autocrine for human HGF/SF and Met demonstrated significantly more rapid uptake and more rapid clearance of the I-125-MAb mixture than tumors expressing one or both murine homologues, reaching a mean tumor to total body activity ratio of > 0.3 by 1 day postinjection. We conclude that radioimmunodetection of tumors autocrine for human HGF/SF and Met is feasible with an I-125-MAb mixture reactive against the ligand-receptor pair.